Identification and validation of risk factors in cold work - Giedraityte, Lina (Luleå, 2005)
There are very few methods available for the assessment of cold exposure and they rely more or less on complex equations for calculating heat balance; therefore, there is a need for new practical methods for the identification and control of cold hazards in workplaces. In the first study, the aim was to test a checklist which enables cold risk assessment based on observations in the workplace. The checklist has seven main sections of cold related risk factors: ‘cold air’, ‘wind/air movements’, ‘contact with cold surfaces’, ‘exposure to water/ liquids/moisture’, ‘protective clothing against cold’, ‘protection of hands/feet/head from cold’ and ‘the use of personal protective equipment’. A total of 82 evaluation sheets were obtained from the field testing (24 from Sweden and 58 from Finland). The subjects found the observational checklist to be a usable tool for cold risk assessment in terms of the time needed to perform the risk assessment procedure, the interference of the method with the observed work, the adequacy of the instructions and the facility of the checklist. In the second study, the aim was to test the checklist at workplaces in a country representing a different approach to safety culture than the one prevailing in Scandinavian countries. A secondary objective was to test whether there was a learning effect reflected in the results recorded in the evaluation sheets when filled in after conducting the cold risk assessment procedure for the first, second and third time. A total of 277 evaluation sheets were obtained from 116 observers from two sawmills in north-western Russia. The observers, similarly to the ones in Finland and Sweden, found the observational checklist to be a usable tool for cold risk assessment in terms of the time needed to perform the risk assessment procedure; the instructions provided for the checklist and to the summary table; the facility of the checklist and summary table and the suitability of the checklist (in regards to the structure and content) in identify cold- related ...